Pengembangan E-Content Berbasis Discovery Learning pada Materi Ikatan Kimia Kelas X SMA/MA - Vika Erlina; Rahadian Zainul (Universitas Negeri Padang, 2022)
This research to develop E-Content based on discovery learning on chemical bonding material for class X SMA/MA. This type of research and development (R&D) using the ADDIE model consists of 5 stages namely analysis, design, development, implementation and evaluation. E-Content is used to help students study remotely due to the Covid-19 pandemic. E-Content also provides learning videos, PPT, books to improve stusent learning activities. E-Content in it there are quiz questions and evaluation questions that can measure studens ability to understand chemical bonding material. The data analysis technique used is in the form of validity and practicality sheets. The content validity test was carried out by 3 chemistry lecturers and 3 chemisrty teachers, while the media validity was carried out by 3 lecturers in the field of technology while the practicality test was carried out by 20 students of class X. The results of the analysis of the content validity sheet, media, practicality by students successively the average score of V was 0.82, 0.91 and 0.84. The data obtained indicate that the E-Content on chemical bonding material is valid and practical.